Interpreting the Psalms: issues and approaches - Johnston, Philip (IVP Academic, 2005)
Psalms interpretation in context -- The Psalms and current study / David M. Howard, Jr -- The Psalms and the genre of ancient near eastern prayers / Tremper Longman III -- The Psalms and key themes -- Distress in the Psalms / Philip Johnston -- The Psalms and praise / James Hely Hutchinson -- The Psalms and the king / Jamie Grant -- The Psalms and the cult / Jerome F. D. Creach -- Symbolism in the Psalms : the cherubim-ark / Craig C. Broyles -- The Psalms and interpretation issues -- The teaching of the Psalms / David G. Firth -- The ethics of the Psalms / Gordon Wenham -- Body idioms and the Psalms / Andy Warren-Rothlin -- Psalm one and Torah-meditation : an invitation to 'sound out' Torah / Michael LeFebvre -- The Psalms and interpretative traditions -- The structure of the psalter / Gerald H. Wilson -- Qumran and the Psalms / Dwight D. Swanson -- The Psalms in the Gospels and Acts / Dale A. Brueggemann -- The targum of Psalms / Timothy Edwards.